THE SYNTHESIS AND CHARACTERIZATION OF ZINC OXIDE THIN FILM DOPING SELENIUM - Miranti Agustin; Ari Sulistyo Rini; Akrajas Ali Umar (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
The selenium-doped ZnO nanomaterial has successfully grown the surface of FTO (Fluorine Tin Oxide) using a seed-mediated hydrothermal method at a temperature of 90°C for 5 hours. In this research, the doping selenium by variation the volume of selenium solution at 0 mL, 0.025 mL dan 0.2 mL. This is an impact on the optical properties and morphology of ZnO nanorods. The samples were characterized using UV-Vis spectroscopy, X-Ray Diffraction and Field Emission Scanning Electron Microscopy (FESEM). The UV-Vis spectra showed that strong absorption occurs in the wavelength range of 300-380 nm. The 0.025 mL Se doped ZnO was the highest absorption compared to other samples. The XRD pattern exhibited five peaks at an angle of 2θ: 31.70°; 34.4°; 36.2°; and 47.5°. representing the orientation of the crystal planes (100), (002), (101), and (102) of hexagonal lattice. The FESEM images showed that Se doped ZnO with hexagonal face shape. The 0.2 mL Se doped ZnO was the most uniform compared to other samples.